Interobserver Agreement on Endoscopic Classification of Oesophageal Varices in Children. Issue 2 (August 2015) - D'Antiga, Lorenzo; Betalli, Pietro; De Angelis, Paola; Davenport, Mark; Di Giorgio, Angelo; McKiernan, Patrick J.; McLin, Valerie; Ravelli, Paolo; Durmaz, Ozlem; Talbotec, Cecile; Sturm, Ekkehard; Woynarowski, Marek; et al.
ABSTRACT Objectives: Data regarding agreement on endoscopic features of oesophageal varices in children with portal hypertension (PH) are scant. The aim of this study was to evaluate endoscopic visualisation and classification of oesophageal varices in children by several European clinicians, to build a rational basis for future multicentre trials. Methods: Endoscopic pictures of the distal oesophagus of 100 children with a clinical diagnosis of PH were distributed to 10 endoscopists. Observers were requested to classify variceal size according to a 3-degree scale (small, medium, and large, class A), a 2-degree scale (small and large, class B), and to recognise red wales (presence or absence, class Red). Overall agreement was considered fair if Fleiss and Cohen κ test was ≥0.30, good if ≥0.40, excellent if ≥0.60, and perfect if ≥0.80. Results: Agreement between observers was fair with class A (κ = 0.34) and class B (κ = 0.38), and good with class Red (κ = 0.49). The agreement was good on presence versus absence of varices (class A = 0.53, class B = 0.48). The agreement among the observers was good in class A when endoscopic features of severe PH (medium and large sizes, red marks) were grouped and compared with mild features (absent and small varices) (κ = 0.58). Conclusions: Experts working in different centres show a fairly good agreement on endoscopic features of PH in children, although a better training of paediatric endoscopists may improve the agreement in grading severity of varices in this setting.